MACHIAVELLIAN CHARACTERS IN DISNEY’S REVERIE - Rahmawanti, Movi Riana (ENGLISH JOURNAL, 2017)
This research tries to discuss the portrayal of Machiavellian manifestations of some villains in Disney?s movies, and to what extent those characters embodied the qualities of a Machiavellian. Using a descriptive qualitative method, this study examines villains in some Disney?s movie namely Prince Hans of the Southern Isles, from Frozen, and Jafar from Arabian Nights. By the end of the research, it can be concluded that some of Disney?s characters employed Machiavellian manifestations varied from time to time. The portrayal of Prince Hans is more narcissists and manipulated than Jafar, and both of them have different way to achieve their goals to get more power. In term of Machiavellian traits, both of them embodied different personalities that somehow led to their downfall. For Hans from Frozen, The most appeared Machiavellian traits are disguise and he uses a lot of trick to reach his goals. Meanwhile, Jafar is more dark and seems cruel in appearance, he uses his power to threat and spread terror